Regional Programme of Action for the Women of Latin America and the Caribbean and other Regional Consensuses (ECLAC SantiagoCL, 2004)
Sets forth a basic package of priority activities for Latin America and the Caribbean that can be carried out in the next five years. Seeks to improve the status of all women in the region, regardless of their age, particularly rural women and those belonging to different population groups, such as indigenous, black, disabled and uprooted women.
Keywords: WOMEN